The Integration of the Nature of Science and Religion to Increase Students' Religious Beliefs in Acquiring Scientific Knowledge at the Elementary School - Tursinawati, Tursinawati; Fitriani, Suci; Safiah, Intan; Widodo, Ari; Sopandi, Wahyu; Amiruddin, M. Hasbi (Jurnal Prima Edukasia, 2024)
Various efforts have been made to increase students' understanding and scientific skills in science learning; however, religion is often ignored. This study seeks to integrate science and religion concepts in increasing students' religious beliefs to acquire scientific knowledge. This study used mixed methods research. The samples, consisting of 100 students and four teachers from four elementary schools in Aceh province, were chosen randomly. Data were collected from student questionnaires, teacher interviews, and observation of learning implementation. The research results found that there has been no integration of the concepts of science and religion by linking NOS (Nature of Science) aspects and religious beliefs in acquiring scientific knowledge in science learning in elementary schools. The integration carried out previously was by integrating the verses of the Qur'an into scientific concepts. The implementation of integrating the concepts of science and religion increased religious beliefs in acquiring scientific knowledge among elementary school students. Most students strongly agree with religious beliefs in acquiring knowledge. Students strongly agree that science is a way to get closer to God. In learning science, teachers should integrate NOS and religious beliefs in acquiring scientific knowledge through impressions of feelings, reasoning, and intuition toward God's creation.  This research should contribute to the understanding of science and NOS concepts related to the topics of science and religion, how scientists work, social culture, moral values, and emotional and spiritual intelligence.